Korean adolescents’ experiences studying abroad and subsequent readjustment to life after returning - Lee, Ji-yeon; Lee, Dong Hun (Frontiers in Psychology, 2024)
Introduction: This qualitative study explored the socio-cultural adjustment and re-adjustment experiences of South Korean adolescents who studied in English-speaking countries and later returned to South Korea.The study interviewed 12 adolescents (6 males, 6 females) aged 12 to 16 who studied in countries such as the U.S., Canada, England, New Zealand, and Australia.The findings highlight the students' adjustment processes abroad, including the initial "honeymoon" phase, followed by crises like language barriers, homesickness, and difficulties in relationships with peers and teachers. Upon returning to Korea, students faced challenges with academic performance, stricter school regulations, and social reintegration, often exacerbated by biases toward those who studied abroad.The study underscores the importance of support systems during both phases and highlights the need for educational interventions that can ease the transition both abroad and at home. This research contributes to understanding the complexities of cross-cultural adjustment and re-entry, especially in the context of adolescents' identity and belonging, suggesting sustainable education system to support students' both abroad and returning process.